The Church Land Programme and Black Theology of Liberation: Solidarity and Suggestions for an Innovative Methodology - Mlambo, Ntandoyenkosi (Religions, 2025)
Black Theology of Liberation, particularly in South Africa, has always been for Black people in the world and produced theological reflections through the lens of Black people. In the evolving scholarship on BTL, there has been challenges in its middle class positionality toward the Black poor and oppressed. The Church Land Programme in Pietermaritzburg was presented with a similar challenge on its positionality in its work on land reform. The CLP’s shift from an organisation working on behalf of the Black poor to working with them may provide suggestions for BTL’s methodology and positionality. This article analyses the Church Land Programme’s community-led publications and how these provide innovative methodological choices for Black Theology of Liberation scholars. Firstly, it explores the Church Land Programme’s history, strategic shifts, and publication partnerships within communities. Secondly, is analyses the publications’ use of stories from within communities. Finally, it discusses new methodological choices in Black Theology of Liberation through lessons from the Church Land Programme’s shift and resultant publications. The results reveal that narratives from below can be promoted in Black Theology of Liberation’s methodology.